EARNINGS AND CASH FLOW IN PREDICTING FINANCIAL DISTRESS - Queensly Malumbeke; Frisky Jeremy Kasingku (UNKLAB Business School, 2022)
This study aimed to test the effect of earnings and cash flow to predict the probability of financial distress. This study examines seven years of financial report investigate the prediction ability of earnings and cash flows to financial distress in a longer period. This study uses manufacturing companies listed in Indonesian Stock Exchange as the sample. Earnings before taxes and operating cash flow ratio data on the 2012-2017 is used to predict financial distress. This research used causal descriptive method and data were analyzed with logistic regression models with SPSS. The results of this study show that earnings have a significant influence in predicting financial distress that occurred in manufacturing sector companies. However, cash flow was not able to predict the financial distress. Keywords: Earnings, cash flow, financial distress Penelitian ini bertujuan untuk menguji pengaruh laba dan arus kas untuk memprediksi probabilitas terjadinya financial distress. Penelitian ini mengkaji laporan keuangan tujuh tahun dengan menyelidiki kemampuan prediksi laba dan arus kas terhadap financial distress dalam periode yang lebih lama. Penelitian ini menggunakan perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia sebagai sampel. Data laba sebelum pajak dan rasio arus kas operasi tahun 2012-2017 digunakan untuk memprediksi financial distress. Penelitian ini menggunakan metode deskriptif kausal dan data dianalisis dengan model regresi logistik dengan bantuan SPSS. Hasil penelitian ini menunjukkan bahwa laba memiliki pengaruh yang signifikan dalam memprediksi financial distress yang terjadi pada perusahaan sektor manufaktur. Namun, arus kas tidak mampu memprediksi kesulitan keuangan. Kata kunci: Laba, arus kas, financial distress